2019
DOI: 10.14326/abe.8.130
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Arm Joint Limitation on Interlimb Coordination during Split-belt Treadmill Walking

Abstract: During walking, arm and leg swings in healthy people are closely coupled temporally by interlimb coordination. A split-belt treadmill contains two belts that can be driven at different velocities, and is used to demonstrate the adaptability of human bipedal locomotion. Previous studies focusing on the use of split-belt treadmills in patients with neurological disorder demonstrated the existence of impaired temporal limb coordination in such patients, but the in uences of neural and nonneural factors on interli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The reduced perturbation magnitude and lack of after-effects in the stabilized groups were not due to a lack of arm swing in this study, as shown by the Restrained arms group. Research has shown that arm movement is coupled to contralateral leg movement in symmetric and asymmetric human walking [37], and that restraining elbow movements in split-belt walking changes inter-limb temporal coordination [38]. The effect of arm movement on dynamic stability in human gait is the theme of an ongoing discussion [39].…”
Section: The Role Of Arm Swing In Locomotor Adaptationmentioning
confidence: 99%
“…The reduced perturbation magnitude and lack of after-effects in the stabilized groups were not due to a lack of arm swing in this study, as shown by the Restrained arms group. Research has shown that arm movement is coupled to contralateral leg movement in symmetric and asymmetric human walking [37], and that restraining elbow movements in split-belt walking changes inter-limb temporal coordination [38]. The effect of arm movement on dynamic stability in human gait is the theme of an ongoing discussion [39].…”
Section: The Role Of Arm Swing In Locomotor Adaptationmentioning
confidence: 99%